The joy of genius : the next step beyond The big leap : a new way to end negative thinking and liberate your true creativity - Hendricks, Gay (Waterside Press, 2018)
Gay Hendricks broke new ground earlier this century with his bestselling classic, The Big Leap, which has become an essential resource for coaches, entrepreneurs, executives and health practitioners around the world. Now, Dr. Hendricks brings you his new work, the next step beyond The Big Leap. The new book shows how to solve two major problems creative people face: how to end negative thinking and how to liberate authentic creativity. The Joy of Genius also shows you how to use the Genius Move, a new navigational tool for reaching the highest level of your potential. If you are committed to bringing forth your innate genius and making your largest possible creative contribution, The Joy of Genius, will become a trusted companion for the journey.